ANALISIS PENDAPATAN DAN KELAYAKAN USAHATANI TOMAT DENGAN PENERAPAN MULSA PELASTIK PERAK DI DESA BORA KECAMATAN SIGI BIROMARU KABUPATEN SIGI - Suwandi, Suwandi; Hadayani, Hadayani; Howara, Dafina (AGROTEKBIS, 2019)
This research intend to analyze the income and the feasibility of tomatoes farming to the application of silver mulsa a Bora village Sigi Biromaru Subdistrick Sigi Regency on June to Agustus 2017. 33 respondents were selected through cencus method. Income analysis used is (p=TR-TC ) and analysis Revenue Cost Ratio (R/C). The result of research revealed that the production of feasibility tomatoes farming is 5,866.66 kg/0.47ha or 12,482.26 kg/ha, the selling price is Rp. 2.500.00/kg. The income of respondent of tomatoes farmers in Bora villages is Rp.14,666,666.67/0.47ha or Rp. 31,205,673.77/ha. Meanwhile, the outcome is Rp. 10,878,666.67/0.47ha or Rp. 22,952,482.27/ha, the income is Rp. 3,879,000.00/0.47ha or Rp. 8,253,191.48/ha. Therefore, it can be cocluded that tomatoes farming through the application of silver mulsa is eligible to be used with Revenue Cost Ratio(R/C) Rp. 1.34 which means that every outcome is Rp. 1 will produce income Rp. 1,34.